2019
DOI: 10.1111/jphp.13032
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of experimental metabolic syndrome induced in rats by orlistat and Corchorus olitorius leaf extract; role of adipo/cytokines

Abstract: Objectives To determine the efficacy of Corchorus olitorius (C. olitorius) leaf extract in the prevention of metabolic syndrome induced in rats by high‐fat diet (HFD) and compare it with that of orlistat. Methods Phytochemical analysis was performed. Effect of orlistat and C. olitorius extract on lipase activity and acute food intake were investigated. Body weight, biochemical parameters and histopathological examination were demonstrated. Key findings Corchorus olitorius extract inhibited the pancreatic lipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Our present study demonstrated that the adiponectin level in the OB group was significantly decreased in comparison to the Normal group, which was parallel to other study [61]. This could be due to the higher inflammatory cytokines in the OB group, which could further suppress the adiponectin level [11]. In addition, adiponectin and leptin are both co-related towards the progression of atherosclerosis [62].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our present study demonstrated that the adiponectin level in the OB group was significantly decreased in comparison to the Normal group, which was parallel to other study [61]. This could be due to the higher inflammatory cytokines in the OB group, which could further suppress the adiponectin level [11]. In addition, adiponectin and leptin are both co-related towards the progression of atherosclerosis [62].…”
Section: Discussionsupporting
confidence: 87%
“…Orlistat acts selectively towards gastrointestinal lipase by preventing the hydrolysis of ingested dietary fat into absorbable free fatty acids and glycerol [10]. For this reason, orlistat has demonstrated its effectiveness in improving obesity parameters such as BMI, lipid profiles, white adipocyte size, and fecal fat excretion in animal models, as well as the complications of obesity such as metabolic syndrome and endothelial dysfunction in human [11][12][13]. Considering its easy availability, cost effectiveness, and significant effect on reducing weight, orlistat has become a standard drug and is the most used obesity drug in the wider population with obesity in comparison to other drugs such as sibutramine, which has been shown to cause adverse cardiovascular effects, as well as phentermine and diethylpropion, which have sympathomimetic effects and only subjected for short term management [14].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to lipase inhibition, the IC50 of the Tintorera grape extracts was slightly higher than some phenolic standards used in this assay (0.14 mg mL −1 for chlorogenic acid, 0.13 mg mL −1 for delphinidin 3-galactoside, and 0.13 mg mL −1 for kuromanin chloride), with the exception of malvidin 3-galactoside, which presented a similar dose (0.16 mg mL −1 ). In fact, it is necessary to emphasize that the IC50 values for common inhibitors such as orlistat was 0.123 mg mL −1 [26], a value close to what we have obtained with 0.16 mg/mL, demonstrating a good inhibitory capacity of the Tintorera grape extract.…”
Section: Biological Activity Of Tintorera Grapes In Vitrosupporting
confidence: 79%
“…Corchorus olitorius known as "Molehiya" in Cyprus (Jew's Mallow, Molukhia, Mulukhiyya, Mloukhiya and Moreheiya in various countries) is an antioxidant plant (Oyedeji et al, 2013). Corchorus olitorius has been reported to be used in alternative therapy and experimental research, with protective or disease preventive effects (Owoyele et al, 2015;Wagdy et al, 2019;Gomaa et al, 2019;Orieke et al, 2020). Chemical composition of Corchorus olitorius, which has antioxidant, antihepatotoxic, antibacterial effect, is rich in vitamin A, vitamin C, fibre, calcium, w-3 fatty acid, iron and other various minerals (Adedosu et al, 2015;Ademiluyi et al, 2015;Mahmoud et al, 2016;Airaodion et al, 2019).…”
Section: Introductionmentioning
confidence: 99%